2017
DOI: 10.1038/srep42778
|View full text |Cite
|
Sign up to set email alerts
|

A new primitive Neornithischian dinosaur from the Jurassic of Patagonia with gut contents

Abstract: We describe a new species of an ornithischian dinosaur, Isaberrysaura mollensis gen. et sp. nov. The specimen, consisting in an almost complete skull and incomplete postcranium was collected from the marine-deltaic deposits of the Los Molles Formation (Toarcian-Bajocian), being the first reported dinosaur for this unit, one of the oldest from Neuquén Basin, and the first neornithischian dinosaur known from the Jurassic of South America. Despite showing a general stegosaurian appearance, the extensive phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 30 publications
0
51
0
Order By: Relevance
“…Fruit and seed morphologies adapted for dispersal by vertebrates appeared before the Mesozoic era (Pennsylvanian period); therefore, herbivorous dinosaurs are the primary candidates considered responsible for seed dispersal in the Mesozoic era (Tiffney , Pu et al ). A set of species of Theropoda have distinctive morphologies adapted for herbivory (Zanno and Makovicky , Pu et al ), whereas some of the theropod and ornithischian dinosaurs show direct evidence of fruit or seed consumption (Zhou and Zhang , Salgado et al ). In addition, carnivorous dinosaurs could have dispersed seeds, either by accidental consumption of seeds or via their consumption of herbivorous animals; this has been confirmed in some extant vertebrates (Nogales et al , van Leeuwen et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Fruit and seed morphologies adapted for dispersal by vertebrates appeared before the Mesozoic era (Pennsylvanian period); therefore, herbivorous dinosaurs are the primary candidates considered responsible for seed dispersal in the Mesozoic era (Tiffney , Pu et al ). A set of species of Theropoda have distinctive morphologies adapted for herbivory (Zanno and Makovicky , Pu et al ), whereas some of the theropod and ornithischian dinosaurs show direct evidence of fruit or seed consumption (Zhou and Zhang , Salgado et al ). In addition, carnivorous dinosaurs could have dispersed seeds, either by accidental consumption of seeds or via their consumption of herbivorous animals; this has been confirmed in some extant vertebrates (Nogales et al , van Leeuwen et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Constraint trees were then written using the 'Force' command in TNT to explore how labile the position of Paranthodon was in each phylogenetic analysis. The significance of the constraint trees was tested using 1000 replications of the Templeton Test (Salgado et al, 2017). Support for groupings was tested using symmetric resampling, which was carried out with a probability of 33% and 1000 replicates on a 'New Technology' search of existing trees.…”
Section: Paranthodonmentioning
confidence: 99%
“…The most recent phylogeny of Stegosauria by Raven and Maidment (2017) showed Paranthodon and Tuojiangosaurus to clade together, a result that was found again here in the one most parsimonious tree of length 279.65 (Analysis E1). Isaberrysaura, the Argentinian dinosaur found as a neornithischian by Salgado et al (2017), was then found in a sister-taxon relationship with Gigantspinosaurus (Analysis E2). However, the strict consensus of the four most parsimonious trees of length 285.38 had a lack of resolution at the base of Eurypoda.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%
See 2 more Smart Citations